2009
DOI: 10.1007/s00244-009-9403-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effect and Biochemical Study of Chlorfluazuron, Oxymatrine, and Spinosad on Honey Bees (Apis mellifera)

Abstract: Under laboratory conditions, the comparative effects of two insect growth regulators, chlorfluazuron and oxymatrine, and spinosad as a biopesticide were examined on honey bee workers (Apis mellifera L.). Separate groups of bees were left for 24 h to feed on 50% sucrose solution containing different concentrations of the tested insecticides, and the lethal concentration that caused 50% mortality (LC(50)) was estimated. The inhibitory effects on acetylcholinesterase (AChE) and adenosine triphosphatase (ATPase) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 43 publications
1
39
0
7
Order By: Relevance
“…The insect nAChRs have long been recognized as potential targets for insecticides, but the widespread use of insecticides can also affect useful, non-target insects, such as the honey bee. The Chinese honey bee, Apis cerana cerana, is an important beneficial insect in agriculture that is constantly exposed to environmental pollution, including insecticides (Rabea et al, 2010). This species exists widely in China, but limited information on nAChRs in the Chinese honey bee is available.…”
Section: Introductionmentioning
confidence: 99%
“…The insect nAChRs have long been recognized as potential targets for insecticides, but the widespread use of insecticides can also affect useful, non-target insects, such as the honey bee. The Chinese honey bee, Apis cerana cerana, is an important beneficial insect in agriculture that is constantly exposed to environmental pollution, including insecticides (Rabea et al, 2010). This species exists widely in China, but limited information on nAChRs in the Chinese honey bee is available.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] For example, oxymatrine is the main effective and toxic alkaloid component derived from the root of Sophora flavescens AIT, which is widely distributed in Asia and the Pacific Islands. [8][9][10] It was previously reported that oxymatrine displays specific pharmacological effects in targeting hepatitis B infections and liver fibrosis. [11][12][13] Furthermore, it has been demonstrated that oxymatrine exerts anti-tumor properties in several cancers via different signaling pathways, such as suppression of proliferation and promotion of apoptosis.…”
mentioning
confidence: 99%
“…It controls Tetranuchus urticae, Spodoptera littoralis, Leucinodes orbonalis, and Liriomyza sativae (Adiroubane & Raghuraman 2008;Asghari Tabari et al 2009;El-Mageed & Shalaby 2011;Medo & Marcic 2013). It is low-toxic for honey bees (Apis mellifera) in comparison to spinosad and chlorfluazuron (Rabea et al 2009). Oxymatrine is more toxic to WFT larvae (especially first instar larvae) than to adults (Gholami 2012).…”
Section: Biology and Problems Concerning Frankliniella Occidentalismentioning
confidence: 99%